Kompetensi Sumber Daya Manusia (SDM) Dalam Meningkatkan Kinerja Tenaga Kependidikan Pada Bagian Akademik Universitas Sam Ratulangi Manado. - Runtu, Anita Christine; Mandey, Jantje; Ogotan, Martha (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract :This research aims to know the performance of produce educators at the Academic University ofSam Ratulangi Manado. " Aspects that should be taken to achieve competence, namely, hard work and agreat desire to want to learn and keep learning without thinking of things that limit us to back off and notwant to evolve, because the science knowledge and skills that will lead us to a success. lazy in Office butshould have a willingness to continue to develop. If we often procrastinate job, lazy in Office and has nowill to develop it will greatly affect our performance. Therefore, with positive thinking for the sake ofimproved performance then with craft, loyalty, as well as creativity can improve performance as work forthe sake of advancing responsibility form the University of Sam Ratulangi University as the pride of NorthSulawesi.In this research uses qualitative research methods in which this research will emphasize researchresults at a depth where the researcher directly involved as an instrument of the research base of theInformant in this research is the head of the academic section of the University of Sam Ratulangi Manado(Informants 1), which is considered able to give further information could also give recommendationsanyone could become a staple in the study informants. u Lo Principal Informants in this study is Part ofthe academic staff of the University of Sam Ratulangi Manado assigned as many as 7 people informant.As for the steps-the steps in the analysis of the data, i.e., what Data still need to be sought, the hypothesisof what needs to be tested, what questions need to be answered, what method should be used to obtain newinformationConclusion based on the above interviews are then compared with the theory and concepts ofCompetence as well as human resource management at connect with Competence human resources inimproving the performance of produce educators at the academic University of Sam Ratulangi Manado,as described later in the tighten up existing theories above it overall indicates that human resources arealready capable in the execution of daily job duties , well, responsible, are to assist and serve, has animpact from the influence of the consciousness of freedom of Association and relationship coaching,managerial competence, cognitive, and personal effectiveness. So the results of this research show that theperformance of produce educators at the academic University of Sam Ratulangi Manado is already good,but even better when retained what already felt good and upgraded again what is felt is still lacking.Referring to the discussion and conclusions in any educational staff is expected to recommend inthe academic section further enhance existing human resources. Don't be satisfied with what we have atthe moment but, let's keep digging up all the potential of ourselves to further improving human resourcesis certainly will also improve our performance. Expected also to the staff of produce educators to be ableto give excellent service to students so that there can be reflected from the human resources which areowned. Expected each produce educators both superiors and subordinates, make up a good workingrelationship among each other so that it can support any work so that it can run well and gainedsatisfactory results without anyone feels aggrieved. Continue to preserve what already exists today, goodnature, self-control, self-confidence, flexibility, and a commitment to the Organization so that the progressof an organization in this case Sam Ratulangi University will be the heartland of the us as well. Need fortrainings on leadership, public service, and managerial employees in order that in this case thecompetence of employees itself can increase through the training.Key words: competence, Human Resources